2000
DOI: 10.1212/wnl.55.3.418
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemia-induced cerebellar dysfunction and quantitative positron emission tomography study

Abstract: In a case of episodic bilateral cerebellar dysfunction caused by hypoglycemia, quantitative dynamic PET study demonstrated decreased glucose uptake-to-utilization ratio and increased leak of glucose in the cerebellum. The cerebellum is not invariably resistant to hypoglycemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…It is generally assumed that the cerebellum is efficient in using glucose to help protect it from the effects of hypoglycemia. One small study contradicts this assumption (41). The cerebellum is involved in cognition, in particular with executive function (42).…”
Section: Discussionmentioning
confidence: 99%
“…It is generally assumed that the cerebellum is efficient in using glucose to help protect it from the effects of hypoglycemia. One small study contradicts this assumption (41). The cerebellum is involved in cognition, in particular with executive function (42).…”
Section: Discussionmentioning
confidence: 99%
“…The only other patient in the literature with normal MRI findings in the setting of hypoglycemia-induced cerebellar dysfunction had normalization of her ataxia within 12 hours of onset. 3 It appears that the neuronal damage in our patient was severe enough to cause prolonged ataxia, however, the damage was reversible as evidenced by the normalization of his ataxia. A question that remains unanswered is whether the relatively normal MRI findings in the setting of hypoglycemia-induced cerebellar dysfunction predict complete recovery as occurred in our patient.…”
Section: Discussionmentioning
confidence: 58%
“…6 The cerebellum is normally protected from hypoglycemia, and several studies in rat and in man have shown differences in glucose metabolism in the cerebellum compared to the cerebrum, providing a physiologic explanation for such protection. 3,8,9 Few other cases have been reported on hypoglycemiainduced cerebellar dysfunction. In those cases, myelinolysis appears to be associated with continued neurologic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations